Graduated opinion about UFF’s Psychology Course (Fractal: Journal of Psychology, 2009)
It shows results of research lead with graduated in the course of Psychology of UFF objecting to investigate their working condition in that period, the contribution of the course for professional insertion, how they evaluate the course and the image they make of the institution. The results gotten with a sample of 38 respondents who answered the proposed instrument shows  that the choice of the course was more because it is a free institution and their option for this career was a personal decision. They consider that the profile of the professional graduated in this institution is good and tend to evaluate the course as “great”. They point to a strong emphasis in the social and political aspects of the profession. They evaluate the professors in a positive way, but they indicate some non satisfaction with the methodology of education used. The initial expectations of these graduated were significantly guided for the work market and they consider that the course helped in their professional career. Almost the totality of the sample is employed and works in the Psychology area in a satisfactory way.